R/V NATSUSHIMA NT06-23 Cruise Data - JAMSTEC (JAMSTEC, 2006)
[CRUISE DATA] This site includes a cruise dataset acquired in NT06-23 on R/V NATSUSHIMA from 2006-12-19 to 2006-12-24.
Observation contents: Bathymetry, Biological Sample, Rock Sample
Keywords: Research cruise; R/V NATSUSHIMA; oceans